Analisis Kompetensi Tenaga Perpustakaan SMA di Gugus 3 Kota Tangerang Selatan di Era Society 5.0 - Aam Mariyamah; Rosiana Nurwa Indah (Program Studi Perpustakaan dan Sains Informasi UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2026)
Library staff competencies have become increasingly important in supporting library transformation in the Society 5.0. However competency develompment for library staff is often not based on comprehensive competency mapping, particularly within the context of school libraries where library personnel have diverse backgrounds and characeristic. This study aims to anallyze the competencies of senior high school library staff in Gugus 3 Tangerang Selatan City using a four-dimensional competency framework consisiting of lifelong learning, technical, managerial, and social competencies. This research employed a mixed methods approch with a case study design. This research employed a mixed methods approach with a case study design. Quantitative data were collected through an online survey involving 19 library staff members. Qualitative data were obtained through observation, documentation, and in-depth interviews with library staff, school principals, and the Head of the Center for the Development of School/Madrasah and Higher Education Libraries (P3SMPT) of the National Library of Indonesia. The findings revealed that lifelong learning competency obtained the highest score (3.1), followed by social competency (2.9), managerial competency (2.5), and technical competency (2.4). These results indicate that the motivation and learning adaptability of senior high school library staff in Gugus 3 Tangerang Selatan City are categorized as very good, while technological readiness and managerial strengthening still require further development. Qualitative analysis further revealed that these conditions are related to the characteristics of library staff, most of whom are teachers assigned additional responsibilities as library managers, as well as the lack of institutional support and strategic library planning within schools. This study demonstrates that the development of library staff competencies should not solely focus on improving individual capabilities but also requires systemic and sustainable strengthening of school library governance. The findings of this study are expected to serve as a basis for developing more contextual competency development strategies for school library staff in accordance with the needs of the Society 5.0 era.